Assessment of Autonomic Functions in Obese Adults - Kaur, Gurmeet; Kaur, Sandeep; Sachdev, Sunil (JK science : journal of medical education and research, 2021)
Material and Methods: This cross-sectional study involved 200 subjects, divided into two groups (n=100 each) on the basis of Body Mass Index (BMI) into control (non-obese) and study (obese) groups. The autonomic nervous system (ANS) plays a major role in the integrated regulation of food intake, involving satiety signals and energy expenditure; thus, ANS dysregulation could be the factor favouring body weight gain. [...]the study of ANS function in obesity is of considerable clinical interest (5). There was statistically high significant difference in the SBP (p = 0.037) and DBP (p = 0.048) between the control group and obese group on OTT (change from lying to erect position) with obese subjects showing significantly more change (fall in blood pressure)